(untitled) (International Journal of Physiotherapy, 2014)
Background: Cervical Traction and Neural Mobilization both have been individually advocated for treatment of Cervical radiculopathy due to their various effects. But the combined effect of these techniques applied simultaneously has not been explored in studies. Hence the purpose is to find the effect of simultaneous application of cervical traction and neural mobilization on improvement in neck pain, radicular symptoms and neck disability in subjects with Cervical Radiculopathy. Methods: An experimental study design, 60 subjects with Unilateral Cervical Radiculopathy and ULTT1 positive for median nerve bias, randomized 20 subjects each into three groups- Group A, B and C respectively. Group A received both Cervical Traction and Neural Mobilization. The Group B received only Mechanical Cervical Traction. The Group C received only Neural Mobilization. The duration of intervention was given 3 treatment sessions per week for four weeks. Outcome measures such as Numerical Pain Rating Scale, Global Rating of Change Scale, Neck Disability Index were measured before, at the end of 2nd and 4th week post treatment. Results: Comparison of post intervention means at 2nd and 4th week of treatment there is a statistically significant (p<0.05) difference in improvement in outcome measures between three groups. Group A subjects shown greater percentage of improvement than Group B and Group C. Conclusion: The present study concludes that simultaneous application of mechanical cervical traction with neural mobilization is more effective in improving pain, functional disability and severity of radicular symptoms than mechanical cervical traction and neural mobilization alone for subjects with Unilateral Cervical Radiculopathy.